2010
DOI: 10.1021/ja1051022
|View full text |Cite
|
Sign up to set email alerts
|

Homoatomic Stella Quadrangula [Tl8]6−in Cs18Tl8O6, Interplay of Spin−Orbit Coupling, and Jahn−Teller Distortion

Abstract: Cs(18)Tl(8)O(6) was synthesized reacting the binary compounds CsTl and Cs(2)O. According to single crystal X-ray analysis, the title compound crystallizes as a novel structure type in the cubic space group I23 and is diamagnetic. The electronic structure of the extended solid and of excised Cs(6)Tl(8) clusters has been examined by relativistic density functional calculations including spin-orbit coupling. Cs(18)Tl(8)O(6) comprises a clusteranion [Tl(8)](6-) in the shape of a tetrahedral star. An isoelectronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
5
32
0
Order By: Relevance
“…In contrast, the nearly ideal octahedral shape of [Tl 6 ] 6– in the title compound and the opening of a band gap can only be reproduced computationally if spin–orbit coupling is considered. A similarly crucial effect of spin–orbit coupling for the correct description of the electronic structure was reported recently for Cs 18 Tl 8 O 6 , containing [Tl 8 ] 6– clusters 11. By comparison of the latter cluster with an isoelectronic, but topologically different one found in Cs 8 Tl 8 O,7 it has been revealed that spin–orbit coupling is a mechanism alternative to Jahn–Teller distortion in order to obtain a closed shell electronic system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the nearly ideal octahedral shape of [Tl 6 ] 6– in the title compound and the opening of a band gap can only be reproduced computationally if spin–orbit coupling is considered. A similarly crucial effect of spin–orbit coupling for the correct description of the electronic structure was reported recently for Cs 18 Tl 8 O 6 , containing [Tl 8 ] 6– clusters 11. By comparison of the latter cluster with an isoelectronic, but topologically different one found in Cs 8 Tl 8 O,7 it has been revealed that spin–orbit coupling is a mechanism alternative to Jahn–Teller distortion in order to obtain a closed shell electronic system.…”
Section: Resultsmentioning
confidence: 99%
“…Cs 4 Tl 2 O was prepared by reaction of the binary compounds CsTl and Cs 2 O. The detailed reaction techniques for preparation of both binary starting compounds have been described previously 11. The mixture of CsTl and Cs 2 O in the molar ratio 1:0.95 (total amount 0.5–1 g) was placed into a tantalum tube, which was sealed under argon with an arc‐welder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Fig. 1), which is known as Hoard dodecahedron [16] and also as stella quadrangula [17,18]. From a structural analysis by means of XRD data through a Rietveld analysis, the refined Mn-O distances for the 4b site appear to be too large compared to what would be expected for Mn 2 þ according to the Shannon radii [36].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent publication we presented a high temperature phase of this compound (h.t.-Mn 3 (VO 4 ) 2 , space group I4 2d) which was shown to exist at temperatures above 946 1C [8]. This phase shows an unusual coordination for the Mn-atoms at the 4b site, which is known as Hoard dodecahedron [16] or as stella quadrangula [17,18] and this site is only half occupied. Co 3 (AsO 4 ) 2 [16] and Mg 3 (AsO 4 ) 2 [19] were previously reported to crystallize in that structure.…”
Section: Introductionmentioning
confidence: 94%